Ameliorate Effects of Li-Fu Formula on IL-6-Mediated Cardiac Hypertrophy in Hamsters Fed with a Hyper-Cholesterol Diet. (10th March 2011) - Cheng, Yi-Chang; Wu, Chieh-His; Kuo, Wei-Wen; Lin, James A.; Wang, Hsueh-Fang; Tsai, Fuu-Jen; Tsai, Chang-Hai; Huang, Chih-Yang; Hsu, Tsai-Ching; Tzang, Bor-Show
Abstract : Hypercholesterolemia diets are considered as major sources to cause cardiac hypertrophy. This study intends to evaluate the effects of Li-Fu formula on cardiac hypertrophy induced by hypercholesterolemia diet. Twenty-four male Golden Syrian hamsters were randomly divided into control, cholesterol and Li-Fu formula groups and fed with different experimental diets for 2 months. Histopathological analysis and western blotting were performed to measure the myocardial architecture, and various cardiac hypertrophy-associated molecules in the excised left ventricle from hamsters. The ratios of whole heart weight/body weight (BW) and left ventricle weight/BW were significantly higher in the cholesterol group but significantly lower in the Li-Fu formula group. The protein levels of both atrial natriuretic peptide and brain natriuretic peptide were significantly increased in the cholesterol group but significantly reduced in the Li-Fu formula group. Additionally, significantly increased interleukin-6, STAT3, MEK5, p-ERK5 and non-cardiomyocyte proliferate signal molecules such as p-MEK and p-ERK, were detected in the cholesterol group but significantly reduced in the Li-Fu formula group. Notably, no significant variations of inflammatory signaling molecules, including p-P38 and p-JNK, were detected in all groups. Our experimental results demonstrated the significant reductions of cardiac hypertrophy and related eccentric hypertrophy signaling, non-cardiomyocyte proliferate signaling in the excised left ventricle of hamsters from the Li-Fu formula. We suggested the protective effects of Li-Fu formula on cardiac hypertrophy that may be useful in prevention or treatment of hypertrophy-associated cardiovascular diseases.